Does China’s Flow of FDI and Institutional Quality Matter for Poverty? Evidence from Sub-Sahara Africa - Iddrisu, K.; Abor, J.Y.; Insaidoo, M.; Banyen, K.T. (Journal of Asian and African Studies, 2023)
The study adds to the discussion on the necessity for Sub-Saharan African (SSA) countries to eradicate poverty, as outlined in SDG 1 and Africa’s Agenda 2063. This contribution was successful in achieving some key objectives. First, we examine the impact of Chinese FDI and institutional quality on the eradication of poverty in SSA. Second, we test empirically whether institutional quality can help Chinese FDI to reduce poverty in SSA. Using an annual dataset for 36 SSA countries for a 20-year period ending in 2020, our pooled OLS results showed that Chinese FDI does not reduce poverty unless there are strong institutions and good governance. Also, the results showed that strong institutions and good governance reduce poverty in SSA. As a result, we recommend that governments establish policies to develop systems and structures that encourage industrialization and attract foreign investors for SSA to reap the full benefits of Chinese FDI.
Research Article
Keywords: Poverty alleviation; institutional quality; Agenda 2063